Brain imaging in myotonic dystrophy type 1 - Kees Okkersen; Darren G. Monckton; Nhu Ngoc Le; Anil M. Tuladhar; Joost Raaphorst; Baziel G.M. van Engelen (2017)
Objective: To systematically review brain imaging studies in myotonic dystrophy type 1 (DM1). Methods: We searched Embase (index period 1974–2016) and MEDLINE (index period 1946–2016) for studies in patients with DM1 using MRI, magnetic resonance spectroscopy (MRS), functional MRI (fMRI), CT, ultrasound, PET, or SPECT. From 81 studies, we extracted clinical characteristics, primary outcomes, clinical-genetic correlations, and information on potential risk of bias. Results were summarized and pooled prevalence of imaging abnormalities was calculated, where possible. Results: In DM1, various imaging changes are widely dispersed throughout the brain, with apparently little anatomical specificity. We found general atrophy and widespread gray matter volume reductions in all 4 cortical lobes, the basal ganglia, and cerebellum. The pooled prevalence of white matter hyperintensities is 70% (95% CI 64–77), compared with 6% (95% CI 3–12) in unaffected controls. DTI shows increased mean diffusivity in all 4 lobes and reduced fractional anisotropy in virtually all major association, projection, and commissural white matter tracts. Functional studies demonstrate reduced glucose uptake and cerebral perfusion in frontal, parietal, and temporal lobes, and abnormal fMRI connectivity patterns that correlate with personality traits. There is significant between-study heterogeneity in terms of imaging methods, which together with the established clinical variability of DM1 may explain divergent results. Longitudinal studies are remarkably scarce. Conclusions: DM1 brains show widespread white and gray matter involvement throughout the brain, which is supported by abnormal resting-state network, PET/SPECT, and MRS parameters. Longitudinal studies evaluating spatiotemporal imaging changes are essential.